Soil vs. canopy seed storage and plant species coexistence in species-rich Australian shrublands - Enright, Neal; Mosner, E.; Miller, Ben; Johnson, Nicole; Lamont, Byron (Ecological Society of America, 2007)
The fire-prone shrublands of southwestern Australia are renowned for their high plant species diversity and prominence of canopy seed storage (serotiny). We compared species richness, abundance, and life history attributes for soil and canopy seed banks in relation to extant vegetation among four sites with different substrate conditions and high species turnover (50 80%) to identify whether this unusual community-level organization of seed storage might contribute to maintenance of high species richness.Soil seed bank (SSB) densities were low to moderate (233 1435 seeds/m2) compared with densities for other Mediterranean-type vegetation and were lowest for sites with highest canopy seed bank (CSB) species richness and lowest nutrient availability, but not richness or abundance of resprouters. Annuals were infrequent in the lowest nutrient sites, but there was no evidence that small SSB size was due to low seed inputs or a trade-off between seed production/storage and seed size in response to low nutrient availability. Sorensen's similarity between SSB and extant vegetation was 26 43% but increased to 54 57% when the CSB was included, representing levels higher than reported for most other ecosystems. Resprouting species were well represented in both the SSB and CSB, and there was no evidence for lower seed production in resprouters than in non-sprouters overall. The SSB and CSB held no species in common and were characterized by markedly different seed dispersal attributes, with winged or small seeds in the CSB and seeds dispersed by ants, birds, and wind (though none with wings) in the SSB. There was no evidence of spatial differentiation in the distribution of seeds of SSB species between vegetated and open microsites that might facilitate species coexistence, but most woody non-sprouters showed aggregation at scales of 1 2 m, implying limited seed dispersal. High similarity between overall seed bank (SSB + CSB) and extant species composition, high number of resprouting species, and seed dispersal processes before (SSB) and after fire (CSB) leading to differential spatial aggregation of post-fire recruits from the two seed bank types may buffer species composition against rapid change and provide a mechanism for maintaining species coexistence at the local scale.